Beyond Nuclear Ribosomal DNA Sequences: Evolution, Taxonomy, and Closest Known Saprobic Relatives of Powdery Mildew Fungi (Erysiphaceae) Inferred From Their First Comprehensive Genome-Scale Phylogenetic Analyses - Vaghefi, Niloofar; Kusch, Stefan; Németh, Márk Z.; Seress, Diána; Braun, Uwe; Takamatsu, Susumu; Panstruga, Ralph; Kiss, Levente (Frontiers in Microbiology, 2022)
Powdery mildew fungi (Erysiphaceae), common obligate biotrophic pathogens of many plants, including important agricultural and horticultural crops, represent a monophyletic lineage within the Ascomycota. Within the Erysiphaceae, molecular phylogenetic relationships and DNA-based species and genera delimitations were up to now mostly based on nuclear ribosomal DNA (nrDNA) phylogenies. This is the first comprehensive genome-scale phylogenetic analysis of this group using 751 single-copy orthologous sequences extracted from 24 selected powdery mildew genomes and 14 additional genomes from Helotiales, the fungal order that includes the Erysiphaceae. Representative genomes of all powdery mildew species with publicly available whole-genome sequencing (WGS) data that were of sufficient quality were included in the analyses. The 24 powdery mildew genomes included in the analysis represented 17 species belonging to eight out of 19 genera recognized within the Erysiphaceae. The epiphytic genera, all but one represented by multiple genomes, belonged each to distinct, well-supported lineages. Three hemiendophytic genera, each represented by a single genome, together formed the hemiendophytic lineage. Out of the 14 other taxa from the Helotiales, Arachnopeziza araneosa, a saprobic species, was the only taxon that grouped together with the 24 genome-sequenced powdery mildew fungi in a monophyletic clade. The close phylogenetic relationship between the Erysiphaceae and Arachnopeziza was revealed earlier by a phylogenomic study of the Leotiomycetes. Further analyses of powdery mildew and Arachnopeziza genomes may discover signatures of the evolutionary processes that have led to obligate biotrophy from a saprobic way of life. A separate phylogeny was produced using the 18S, 5.8S, and 28S nrDNA sequences of the same set of powdery mildew specimens and compared to the genome-scale phylogeny. The nrDNA phylogeny was largely congruent to the phylogeny produced using 751 orthologs. This part of the study has revealed multiple contamination and other quality issues in some powdery mildew genomes. We recommend that the presence of 28S, internal transcribed spacer (ITS), and 18S nrDNA sequences in powdery mildew WGS datasets that are identical to those determined by Sanger sequencing should be used to assess the quality of assemblies, in addition to the commonly used Benchmarking Universal Single-Copy Orthologs (BUSCO) values.